Sulfur containing mixed wastes in anaerobic processing by new immobilized synthetic consortia. (October 2022) - Maslova, Olga; Senko, Olga; Stepanov, Nikolay; Gladchenko, Marina; Gaydamaka, Sergey; Akopyan, Argam; Eseva, Ekaterina; Anisimov, Alexander; Efremenko, Elena
Graphical abstract: Highlights: S-organic extracts from oxidized petroleum fractions were utilized in methanogenesis. Chicken manure was utilized as co-substrate in methanogenesis of S-organic extracts. Increased S-loading of methanogenesis was demonstrated using petroleum extracts. Immobilized synthetic DEAMOX consortium was successfully used for the first time. Methanogenic and DEAMOX processes provided deep conversion of C, S, N -complex wastes. Abstract: Methanogenic biotransformation of unusual substrates (sulfur (S)-containing wastes: non-purified vacuum gas oil, straight-run gasoline fraction (Naphtha), gas condensate, and straight-run diesel fraction) coming from oil industry after their oxidative desulfurization was investigated. Nitrogen-containing wastes (hydrolysates of chicken manure and Chlorella vulgaris biomass) were added as co-substrates to mixture with oil industry wastes. The 100 % conversion of S-organic compounds to inorganic sulfide accumulated in the reaction liquid medium was achieved with simultaneous production of biogas containing high methane percent (greater than 70 %). Polishing of effluents from methane tank was carried out by denitrifying oxidation of ammonium (DEAMOX). The high process efficiency was due to use of original immobilized artificial consortia at the stage of methanogenesis and DEAMOX. This study reveals the real potential in the processing of very complex mixtures of large-scale wastes, usually inhibiting methanogenesis, by developing biocatalysts based on synthetic biology approaches.